PENGEMBANGAN USAHA BUMDESA MASYARAKAT MADANI SEJAHTERA DAN PELAPORAN KEUANGAN MENUJU PENCAPAIAN SDGs - Khuzaini, Khuzaini; Yani, Prawita; Mukhlis, Iqbal Ramadhani (Jurnal KeDayMas: Kemitraan dan Pemberdayaan Masyarakat, 2024)
BUMDES Masyarakat Madani Sejahtera is a business entity initiated by Desa Janti in Sidoarjo- East Java. However, recently BUMDES has an issue for not being able normally operate and provide financial statement as it used to. BUMDes has a retail business which sell daily items to the village. The community service team identify this issue and attempt to solve it. They developed online Post of Sales (POS) for efficiency and effectivity. At the same time the other member of the team which concentrated in accounting assist BUMDes to provide financial statement in accordance with Indonesian financial standard. The team were using collaborative approach which began with mapping the issue and continued with workshop for POS system and the financial statement template, assist BUMDes to use both POS system and financial statement template and the last one to find out how they use it by held monitoring and evaluation activity. At the end, BUMDes revenue and equity have significantly increasing compared to the previous period each 20% and 50%, BUMDes has their own POS system and could provide financial statement in accordance to SAK EMKM. This achievement overall can be used as an acceleration to reach SDGs in Desa Janti.